2002
DOI: 10.1207/s15327027hc1403_5
|View full text |Cite
|
Sign up to set email alerts
|

Women's Perceptions of the Risks of Age-Related Diseases, Including Breast Cancer: Reports from a 3-Year Research Study

Abstract: Misperceptions of health risks lead many women to misunderstand their risks and fail to take appropriate measures to prevent or treat many diseases. This article analyzes the impact of various sources of information on the perceptions and misperceptions of women regarding the risks of age-related diseases. This article shows that most of the women respondents held incorrect beliefs about their risk of heart disease, breast and lung cancer, and osteoporosis; half held inaccurate beliefs about disease-related st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 20 publications
7
36
0
1
Order By: Relevance
“…Moyer, Greener, Beauvais, and Salovey (1995) found inaccuracies in two-thirds of the news coverage of breast cancer. Second, some coverage simply omits information; Covello and Peters (2002;see also Molitor, 1993) show that journalists exclude important background information or critical facts in their coverage. Third, news coverage tends to exaggerate or sensationalize (Schwartz, Woloshin, & Baczek, 2002).…”
Section: News Coverage and Health Issue Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moyer, Greener, Beauvais, and Salovey (1995) found inaccuracies in two-thirds of the news coverage of breast cancer. Second, some coverage simply omits information; Covello and Peters (2002;see also Molitor, 1993) show that journalists exclude important background information or critical facts in their coverage. Third, news coverage tends to exaggerate or sensationalize (Schwartz, Woloshin, & Baczek, 2002).…”
Section: News Coverage and Health Issue Perceptionmentioning
confidence: 99%
“…Mass media provide the main source of health information, in that approximately 80% of the public rely on general media (television, magazines, newspapers) for information about health topics-greater than the percentage who rely on physicians (Covello & Peters, 2002). A 2002 survey by the Pew Research Center also indicated that 71% of Americans closely follow health news (Mebane, 2003).…”
mentioning
confidence: 99%
“…Covello and Peters (2002) stated that the people tend to consider media sources to be unreliable, responding to oversimplified and contradictory health information with ''confusion, hyper vigilance, anxiety, stress, distrust of science and medicine'' (p. 392). Being exposed to conflicting drinking messages, college students may also become confused about the messages, which may influence their attitudes and drinking behaviors.…”
Section: Rationalementioning
confidence: 99%
“…1 In the United States alone, CVD results in both direct and indirect health care costs and productivity loss amounting to $274 billion annually. 2 The therapy evaluation and clinical data analysis are important to the cerebrovascular and cardiovascular pathologies diagnosis; and have attracted significant attention amongst the health and science community. 3,4 Ultrasound (US) has been employed as a routine examination for inexpensive non-invasive clinical diagnosis of atherosclerosis (the hardening of the arteries).…”
Section: Introductionmentioning
confidence: 99%